C++ Reactive Programming : Design concurrent and asynchronous applications using the RxCpp library and Modern C++17 /: Design concurrent and asynchronous applications using the RxCpp library and Modern C++17. (2018) - Abraham, Peter; Pai, Praseed
No abstract available